12.9k views
2 votes
Choose an equation that would be used to solve 0 = -x2 + 10x – 8 (x + 25)2 = –8 (x – 5)2 = 17 (x – 10)2 = 25

User Magdaline
by
5.1k points

2 Answers

3 votes

Answer:

b

Explanation:

User Luay Abdulraheem
by
5.2k points
6 votes

Answer:

Completing the square the equation that would be used to solve 0=-x^2+10x-8 is (x-5)^2=17 (Second option).

Explanation:

0=-x^2+10x-8

Moving the terms with the variable x to the left side of the equation:

0+x^2-10x=-x^2+10x-8+x^2+10x

x^2-10x=-8

Adding both sides of the equation the square of the half of the coefficient of "x" to complete the square on the left side of the equation:

x^2-10x+(10/2)^2=-8+(10/2)^2

x^2-10x+(5)^2=-8+(5)^2

x^2-10x+25=-8+25

x^2-10x+25=17 (1)

Using that (x-a)^2=x^2-2ax+a^2 with

2a=10→2a/2=10/2→a=5

or a^2=25→sqrt(a^2)=sqrt(25)→a=5

x^2-10x+25=(x-5)^2

Then replacing x^2-10x+25 by (x-5)^2 in the equation (1)

(1) (x-5)^2=17

User Nathan Basanese
by
4.9k points